2006
DOI: 10.1016/j.cbpb.2005.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Plasma peptidylglycine alpha-amidating monooxygenase (PAM) and ceruloplasmin are affected by age and copper status in rats and mice

Abstract: In an attempt to identify a sensitive and improved marker of mammalian copper status during neonatal development experiments compared two plasma cuproenzymes, peptidylglycine α-amidating monooxygenase (PAM ), an enzyme involved in peptide posttranslational activation, to ceruloplasmin (Cp), a ferroxidase involved in iron mobilization. Dietary Cu deficiency (Cu−) was studied in dams and offspring at postnatal age 3 (P3), P12, and P28. Rodent Cp activity rose during lactation whereas PAM activity fell. Reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
2
24
1
Order By: Relevance
“…Previous work from our lab with similar Cu− rat pups demonstrated lower liver iron earlier, at P3 and P12 (Prohaska and Broderius 2006). This suggests that the accumulation of liver iron associated with copper deficiency occurs only in older mammals.…”
Section: Discussionsupporting
confidence: 57%
“…Previous work from our lab with similar Cu− rat pups demonstrated lower liver iron earlier, at P3 and P12 (Prohaska and Broderius 2006). This suggests that the accumulation of liver iron associated with copper deficiency occurs only in older mammals.…”
Section: Discussionsupporting
confidence: 57%
“…Although, in the current studies restriction of copper in mice began only shortly before birth, prior studies with full gestational copper deprivation also failed to show a reduction in brain iron in suckling mouse pups despite severe copper deficiency (Prohaska, 1983). Furthermore, previous comparisons of Cu-rat and mouse dams showed that mouse dams were equally, if not more, copper deficient compared to rats following the same nutritional protocols used in the current studies (Prohaska and Broderius, 2006).…”
Section: Discussionmentioning
confidence: 54%
“…Thus, it is possible that Cu-suckling mammals are iron deficient (Pyatskowit and Prohaska, 2008). Supportive evidence of this idea was the observation that liver iron is lower in Cu-rodents at P3 (Prohaska and Broderius, 2006). Others have also recently shown that fetal liver iron is lower in Cu-rat pups (Andersen et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Copper (Cu) is one of these micronutrients that is essential for all biological systems and serves as a cofactor for many mammalian enzymes (Prohaska, 2006). Ewes grazing on pastures low in Cu delivered lambs suffering from neonatal ataxia (Bennetts and Chapman, 1937).…”
Section: Introductionmentioning
confidence: 99%